Microbleeds and the Effect of Anticoagulation in Patients With Embolic Stroke of Undetermined Source: An Exploratory Analysis of the NAVIGATE ESUS Randomized Clinical Trial - Shoamanesh, Ashkan; Hart, Robert G; Connolly, Stuart J; Kasner, Scott E; Smith, Eric E; Martí-Fàbregas, Joan; Liu, Yan Yun; Uchiyama, Shinichiro; Mikulik, Robert; Veltkamp, Roland; O'Donnell, Martin J; Ntaios, George; et al. (JAMA neurology, 2021)
IMPORTANCE: The reported associations of cerebral microbleeds with recurrent stroke and intracerebral hemorrhage have raised concerns regarding antithrombotic treatment in patients with a history of stroke and microbleeds on magnetic resonance imaging. OBJECTIVE: To characterize microbleeds in embolic strokes of undetermined source (ESUS) and report interactions between microbleeds and the effects of random assignment to anticoagulant vs antiplatelet therapy. DESIGN, SETTING, AND PARTICIPANTS: Subgroup analyses of the New Approach Rivaroxaban Inhibition of Factor Xa in a Global Trial vs Aspirin to Prevent Embolism in ESUS (NAVIGATE ESUS) international, double-blind, randomized, event-driven phase 3 clinical trial. Participants were enrolled between December 2014 and September 2017 and followed up for a median of 11 months. The study setting included 459 stroke recruitment centers in 31 countries. Patients aged 50 years or older who had neuroimaging-confirmed ESUS between 7 days and 6 months before screening were eligible. Of these 7213 NAVIGATE ESUS participants, 3699 (51%) had information on cerebral microbleeds reported on their baseline clinical magnetic resonance imaging and were eligible for these analyses. Patients with a prior history of symptomatic intracerebral hemorrhage were excluded from the NAVIGATE ESUS trial. INTERVENTIONS: Rivaroxaban, 15 mg, compared with aspirin, 100 mg, daily. MAIN OUTCOMES AND MEASURES: The primary outcome was recurrent stroke. Secondary outcomes were ischemic stroke, intracerebral hemorrhage, and all-cause mortality. RESULTS: Microbleeds were present in 395 of 3699 participants (11%). Of patients with cerebral microbleeds, mean (SD) age was 69.5 (9.4) years, 241 were men (61%), and 201 were White (51%). Advancing age (odds ratio [OR] per year, 1.03; 95% CI, 1.01-1.04), East Asian race/ethnicity (OR, 1.57; 95% CI, 1.04-2.37), hypertension (OR, 2.20; 95% CI, 1.54-3.15), multiterritorial infarcts (OR, 1.95; 95% CI, 1.42-2.67), chronic infarcts (OR, 1.78; 95% CI, 1.42-2.23), and occult intracerebral hemorrhage (OR, 5.23; 95% CI, 2.76-9.90) were independently associated with microbleeds. The presence of microbleeds was associated with a 1.5-fold increased risk of recurrent stroke (hazard ratio [HR], 1.5; 95% CI, 1.0-2.3), a 4-fold risk of intracerebral hemorrhage (HR, 4.2; 95% CI, 1.3-13.9), a 2-fold risk of all-cause mortality (HR, 2.1; 95% CI, 1.1-4.3), and strictly lobar microbleeds with an approximately 2.5-fold risk of ischemic stroke (HR, 2.3; 95% CI, 1.3-4.3). There were no interactions between microbleeds and treatment assignments for recurrent stroke, ischemic stroke, or all-cause mortality. The HR of intracerebral hemorrhage on rivaroxaban was similar between persons with microbleeds (HR, 3.1; 95% CI, 0.3-30.0) and persons without microbleeds (HR, 3.0; 95% CI, 0.6-14.7; interaction P = .97). CONCLUSIONS AND RELEVANCE: Microbleeds mark an increased risk of recurrent stroke, ischemic stroke, intracerebral hemorrhage, and mortality in ESUS but do not appear to influence effects of rivaroxaban on clinical outcomes. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02313909.
Keywords: Recurrence; Male; cerebrální krvácení; Middle Aged; Aspirin; antikoagulancia; prevalence; Aged; mužské pohlaví; senioři; recidiva; dvojitá slepá metoda; Rivaroxaban; lidé; ženské pohlaví; Anticoagulants; Humans; Prevalence; Cerebral Hemorrhage; Double-Blind Method; Female; lidé středního věku; embolická cévní mozková příhoda; Embolic Stroke; rivaroxaban